Migration and the making of global Christianity - Hanciles, Jehu., 1964- (Grand Rapids, Michigan. : : William. B. Eerdmans Publishing Company, 2021)
"A socio-historical study of the spread of Christianity through the lens of human migration and intercultural exchange"--
Includes bibliographical references and index.
Keywords: Emigration and immigration -- Religious aspects -- Christianity; Globalization -- Religious aspects -- Christianity; Christianity and culture